ASEAN ECONOMIC COMMUNITY 2015: NEEDS ANALYSIS OF UNIVERSITAS INDONESIA’S ENGINEERING STUDENTS - Araminta, Lavinia DW; Halimi, Sisilia Setiawati (Universitas Pendidikan Indonesia, 2015)
Prior to the ASEAN Economic Community in the end of 2015, one of the keys for Indonesian engineers to outrank engineers from other ASEAN countries is mastering English language skills. This study aims at analyzing the English needs of undergraduate engineering students at Universitas Indonesia. Questionnaires and semi-structured interviews were used as the data collection methods. The questionnaires were spread to 111 alumni and 150 students from the Faculty of Engineering. The interviews were conducted with HRD from a multinational company, HRD from a local company, three heads of departments, and two lecturers from the Faculty of Engineering. The research reveals that students’ needs of English language learning are considered not as high as their needs of English language use. The recommendation given to the Faculty of Engineering is to conduct an optional course on English for Professional Purposes, and the course is to be handled by professional English teachers helped by the lecturers from the Faculty of Engineering.